A Literature Review on the Effectiveness of Interactive Media in Elementary School Science Learning - Utami, Dwi Fajar; Sutikno, Putri Yanuarita; Widiarti, Nuni; Yuwono, Agus (Universitas Veteran Bangun Nusantara, 2025)
The use of interactive media has emerged as a viable way to improve the efficacy of science education. However, the use of various interactive media needs to be analyzed in depth regarding its effectiveness. This study aims to analyze the effectiveness of various interactive media created and used in science teaching in elementary schools over the past five years is the purpose of this study. The research method used is literature review analysis through several related research publications published in domestic and foreign journals indexed by SINTA. According to the analysis of the findings of 25 articles, interactive media—including PhET simulations, multimedia centered on digital literacy, interactive applications, and animated films—have been successful. Thus, interactive media is effectively used for science learning in elementary schools. This study contributes at developing interactive, adaptive, innovative, creative, and efficient learning media according to learners' needs in order to enhance the quality of science education in elementary schools.